2016
DOI: 10.1111/cup.12864
|View full text |Cite
|
Sign up to set email alerts
|

Erythema multiforme‐like cutaneous lesions in monomorphic epitheliotropic intestinal T‐cell lymphoma: a rare case report

Abstract: Monomorphic epitheliotropic intestinal T-cell lymphoma (MEITL), also known as Type II enteropathy-associated T-cell lymphoma (EATL), is an aggressive peripheral T-cell lymphoma. EATL generally presents in adults with gastrointestinal symptoms. Skin involvement is very rare, found only in approximately five percent of patients. The authors report a 67-year-old Asian male who presented with chronic diarrhea and developed erythema multiforme-like cutaneous lesions. A skin biopsy revealed extensive pagetoid spread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Treatment regimens mainly consisted of various chemotherapy regimens with 33% of patients receiving stem cell transplants. Unfortunately, survival after diagnosis was poor and ranged from 5 d to 3 yr despite therapy (Table 1) [9][10][11][12][13][14] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment regimens mainly consisted of various chemotherapy regimens with 33% of patients receiving stem cell transplants. Unfortunately, survival after diagnosis was poor and ranged from 5 d to 3 yr despite therapy (Table 1) [9][10][11][12][13][14] .…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [9] 2016, Singapore Aiempanakit et al [11] 2017, Thialand 67 y/o, Male Chronic diarrhea and weight loss…”
Section: History Of Celiac Disease? Treatment Prognosis After Diagnosismentioning
confidence: 99%
“…For differential diagnosis, cutaneous lymphomas [ 14 ], atypical pityriasis rosea [ 15 ], bullous pemphigoid [ 16 ], and lupus erythematosus [ 17 ] must be considered. Histopathology and immune serology allow differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the immunophenotypic study of this case did not include any cytotoxic markers, it might well represent a further example of pCAECD8+ CTCL presenting with EM‐like lesions. Interestingly, a wider PubMed search also revealed that EM‐like cutaneous lesions may be a clinical presenting feature of other T‐cell malignancies, such as aggressive mature T‐cell and NK/T‐cell lymphoma, adult T‐cell lymphoma/leukemia, refractory celiac disease, extra‐nodal NK/T‐cell lymphoma and monomorphic epitheliotropic intestinal T‐cell lymphoma, reflecting the functional attributes of the neoplastic lymphocytes that can recapitulate, at least in part, the clinical aspects of some cytotoxic, CD8+ T‐cell mediated, reactive skin disorders …”
Section: Discussionmentioning
confidence: 99%
“…15,19 Our case had CD2−/CD7+ CD15+ and a partially double CD4/CD8 negative phenotype, reinforcing the previous observations. 24 reflecting the functional attributes of the neoplastic lymphocytes that can recapitulate, at least in part, the clinical aspects of some cytotoxic, CD8+ T-cell mediated, reactive skin disorders. [25][26][27] An accurate and timely diagnosis of pCAE-CD8+ CTCL is crucial, as aggressive treatment strategies, such as multiagent chemotherapy and allogeneic stem-cell transplantation in selected cases might be considered and discussed at an early stage of the disease.…”
mentioning
confidence: 99%